Subharmonic Solutions of Nonautonomous Second Order Differential Equations with Singular Nonlinearities - N. Daoudi-Merzagui; F. Derrab; A. Boucherif (Abstract and Applied Analysis)
We discuss the existence of subharmonic solutions for nonautonomous second order differential equations with singular nonlinearities. Simple sufficient conditions are provided enable us to obtain infinitely many distinct subharmonic solutions. Our approach is based on a variational method, in particular the saddle point theorem.